Stability improvement on industrial load using current controlled voltage regulator. (2020) - Sankar, S.; Saravana Kumar, M.N.; Sangeetha, S.; Radhika, S.; Prabhu, P.
Abstract: In this paper, we considered an industrial load with 33 bus system. This system introduces the modeling of the Current Controlled Voltage Regulator in the load flow calculations for steady-state voltage compensation and loss reduction. Here the performance of the system involves the various ranges of maximum capacity and modeling of this system in its maximum rating of reactive power injection is derived. During this analysis, the proposed fuzzy expert system, generator speed deviation, and its derivative are chosen as input signals to fuzzy logic based power system stabilizer. In this approach centers of membership functions and the parameters of the fuzzy logic controllers have been tuned using a genetic algorithm. Inclusion of GA in tuning fuzzy logic based power system stabilizer will provide good damping and significantly reduces computational time in the design process. Simulation results on a multimachine system subjected to small perturbation and three-phase fault show the effectiveness and robustness of the proposed PSS over a wide range of operating conditions and system configurations.